Komoditi Unggulan Buah-Buahan Perbatasan Indonesia Timor Leste Kabupaten Timor Tengah Utara (Studi Kasus Desa Eban) - Sipayung, Boanerges Putra; Taena, Werenfridus; Joka, Umbu; Maulana, Achmad Subchiandi (Agriprimatech, 2022)
Horticultural commodities, especially fruits, can be a source of increasing income for farmers in West Miomaffo District. This study aims to determine the main commodity of fruit in Eban Village, West Miomaffo District. The implementation of this research is from June to September 2021. The number of samples of this research is 20. The method used in this research is descriptive quantitative analysis with the Dynamic Location Quotient (DLQ) and Analytical Hierarchy Process (AHP) methods. The results showed that the potential fruit commodities in Eban Village were oranges, mangoes, avocados, and jackfruit. Oranges are the most superior fruit commodity in Eban Village with a weight value of 45.0%.